Sexual behavior factors that influence the incidence of HIV/AIDS in men's groups’ male sex - Efi Sarfiani; Dian Meiliani Yulis; Besse Yuliana (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: HIV/AIDS remains a significant public health problem in the world, including in Indonesia. The disease is spread through various pathways, but one of the groups most vulnerable to infection is Men Who Have Sex with Men (MSM). This study aims to analyze the influence of sexual behavior on the incidence of HIV/AIDS in the Men Having Sex with Men (MSM) group. Research Methodology: This type of research is quantitative research with a case-control research design. The population in this study consisted of cases and a control population. The population of cases in this study were all groups of Men Who Have Sex with Men (MSM) who had undergone an HIV test with positive (+) HIV test results and had taken ARV treatment at the Kendari City Regional Hospital for the last 6 (six) months and were domiciled as many as 349 people. Result: The results of the study showed that there was an influence of condom use (OR = 7.154), number of sexual partners (OR = 21,000), anal sex (OR = 7.042), and oral sex (OR = 3.367) on the incidence of HIV/AIDS in the Men Sex Men group. Conclusion: The conclusion is that the sexual behavior of using condoms, number of sexual partners, anal sex, and oral sex are risk factors for the occurrence of HIV/AIDS in the group of men having sex with men. Therefore, individuals in this group need to receive education about the risks, as well as effective prevention methods, such as consistent condom use, routine HIV testing, and open communication with sexual partners.